Lupus-like autoimmune disease caused by a lack of Xkr8, a caspase-dependent phospholipid scramblase - Kawano, Mahiru (Proc Natl Acad Sci U S A, 2018)
Apoptotic cells expose phosphatidylserine (PtdSer) on their cell surface and are recognized by macrophages for clearance. Xkr8 is a scramblase that exposes PtdSer in a caspase-dependent manner. Here, we found that among the three Xkr members with caspase-dependent scramblase activity, mouse hematopoietic cells express only Xkr8. The PtdSer exposure of apoptotic thymocytes, splenocytes, and neutrophils was strongly reduced when Xkr8 was absent. While wild-type apoptotic lymphocytes and neutrophils were efficiently engulfed in vitro by phagocytes expressing Tim4 and MerTK, Xkr8-deficient apoptotic cells were hardly engulfed by these phagocytes. Accordingly, the number of apoptotic thymocytes in the thymus and neutrophils in the peritoneal cavity of the zymosan-treated mice was significantly increased in Xkr8-deficient mice. The percentage of CD62L(lo) senescent neutrophils was increased in the spleen of Xkr8-null mice, especially after the treatment with granulocyte colony-stimulating factor. Xkr8-null mice on an MRL background showed high levels of autoantibodies, splenomegaly with high levels of effector CD4 T cells, and glomerulonephritis development with immune-complex deposition at glomeruli. These results indicate that the Xkr8-mediated PtdSer exposure in apoptotic lymphocytes and aged neutrophils is essential for their clearance, and its defect activates the immune system, leading to lupus-like autoimmune disease.